Flight testing verification of lateral-directional dynamic stability of gliding birds due to wing dihedral - Wei, Chenhao; Lin, Gang; Huang, Jun; Song, Lei; Smith, Howard (Emerald, 2022)
Purpose Unlike conventional aircraft, birds can glide without a vertical tail. The purpose of this paper is to analyse the influence of dihedral angle spanwise distribution on lateral-directional dynamic stability by the simulation, calculation in the development of the bird-inspired aircraft and the flight testing. Design/methodology/approach The gliding magnificent frigatebird (Fregata magnificens) was selected as the study object. The geometric and mass model of the study object were developed. Stability derivatives and moments of inertia were obtained. The lateral-directional stability was assessed under different spanwise distributions of dihedral angle. A bird-inspired aircraft was developed, and a flight test was carried out to verify the analysed results. Findings The results show that spanwise distribution changing of dihedral angle has influence on the lateral-directional mode stability. All of the analysed configurations have convergent Dutch roll mode and rolling mode. The key role of dihedral angle changing is to achieve a convergent spiral mode. Flight test results show that the bird-inspired aircraft has a well-convergent Dutch roll mode. Practical implications The theory that birds can achieve its lateral-directional stability by changing its dihedral angle spanwise distribution may explain the stability mechanism of gliding birds. Originality/value This paper helps to improve the understanding of bird gliding stability mechanism and provides bio-inspired solutions in aircraft designing.
Keywords: dynamic stability; locomotion mode; dihedral angle; bird-inspired aircraft; gliding bird